Analisis Penerapan Good Corporate Governance Dalam Mendukung Keberlanjutan Bisnis Pada PT Berlina Tbk. - Deby , Shara Eva; Sintha, Lis (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the implementation of Good Corporate Governance (GCG) in supporting business sustainability at PT Berlina Tbk. Using a qualitative case study approach, data were collected from annual reports, sustainability reports, governance reports, and relevant literature, and analyzed through content analysis. The findings indicate that PT Berlina Tbk consistently applies the principles of transparency, accountability, responsibility, independence, and fairness, supported by effective governance structures and risk management. These practices enhance economic, social, and environmental sustainability. The study implies that effective GCG serves as a strategic foundation for strengthening corporate resilience and achieving long-term business sustainability.